Μια Νέα Εποχή για το Ελληνικό Επιστημονικό Περιοδικό «ΑΚΤΙΝΟΤΕΧΝΟΛΟΓΙΑ» - Γεωργιάδης, Κωνσταντίνος; Δρακουλίδου, Στέλλα; Malamateniou, Christina; Κωνσταντινίδης, Κλεάνθης (Ακτινοτεχνολογία, 2024)
Δεν υπάρχει διαθέσιμη περίληψη